Revista de Revistas. - L Bautista (Asociacion Espanola de Neuropsiquiatria, 1989)
Revisión de publicaciones de mayo de 1989 -Acta Psychiatrica Scandinavica, vol. 79, n.O 5, may, 1989. -American Journal of Psychiatry, vol. 146, n.O 5, may, 1989. -Archives of General Psychiatry, vol. 46, may, 1989. -British Journal ofPsychiatry, vol. 154, may, 1989. -Family Process, vol. 28, n.O 2, june, 1989. -Hospital and Community, vol. 40, n.O 5, may, 1989.